Detection of Covid-19 in Children in Early January 2020 in Wuhan, China - Liu, Weiyong; Zhang, Qi; Chen, Junbo; Xiang, Rong; Song, Huijuan; Shu, Sainan; Chen, Ling; Liang, Lu; Zhou, Jiaxin; You, Lei; Wu, Peng; Zhang, Bo; et al. (The New England journal of medicine, 2020)
A retrospective analysis of routine surveillance data involving children hospitalized in central Wuhan, China, for acute lower respiratory infection in early January 2020 revealed six cases of Covid-19. The authors report clinical characteristics of the children and laboratory data.